2008
DOI: 10.1128/jb.00301-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Global Transcriptional Regulator PrrA inRhodobacter sphaeroides2.4.1: Combined Transcriptome and Proteome Analysis

Abstract: The PrrBA two-component regulatory system is a major global regulator in Rhodobacter sphaeroides 2.4.1. Here we have compared the transcriptome and proteome profiles of the wild-type (WT) and mutant PrrA2 cells grown anaerobically in the dark with dimethyl sulfoxide as an electron acceptor. Approximately 25% of the genes present in the PrrA2 genome are regulated by PrrA at the transcriptional level, either directly or indirectly, by twofold or more relative to the WT. The genes affected are widespread througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 79 publications
9
78
1
Order By: Relevance
“…The sequence CGCTGCCAGCC was identified as a potential RoxR box, with the underlined hexamer highly conserved. This sequence differs from sequences proposed in Bradyrhizobium japonicum and Rhodobacter sphaeroides, where a degenerate hexamer followed by a pentamer located at a variable distance has been described as a binding site for the RoxR orthologs RegR and PrrA (10,19). Sequences resembling the consensus can be found both in the cioA and the ddcA promoters (CCC TGCGATCG and CGTGCCATGCC, respectively; nucleotides identical to the consensus sequence are underlined).…”
Section: Discussionmentioning
confidence: 60%
“…The sequence CGCTGCCAGCC was identified as a potential RoxR box, with the underlined hexamer highly conserved. This sequence differs from sequences proposed in Bradyrhizobium japonicum and Rhodobacter sphaeroides, where a degenerate hexamer followed by a pentamer located at a variable distance has been described as a binding site for the RoxR orthologs RegR and PrrA (10,19). Sequences resembling the consensus can be found both in the cioA and the ddcA promoters (CCC TGCGATCG and CGTGCCATGCC, respectively; nucleotides identical to the consensus sequence are underlined).…”
Section: Discussionmentioning
confidence: 60%
“…More recently CryB, a member of a newly described cryptochrome family (15), was shown to affect expression of photosynthesis genes in R. sphaeroides and to interact with AppA (16,17). Remarkably, the different signaling pathways for control of photosynthesis genes are also interconnected, e.g., the appA gene is controlled by PrrA (18,19) and a PpsR binding site is located in the ppaA promoter region (20). Thus, a complex network comprising several regulatory proteins controls the formation of the photosynthetic apparatus.…”
mentioning
confidence: 99%
“…Recently, Eraso et al provided an elegant description of the transcriptome and proteome of cells lacking PrrA (10). We hope that the present study will provide the impetus for further transcriptome and proteome investigations directed toward resolving the gene sets subject to each of the two modi operandi of PrrA.…”
Section: Discussionmentioning
confidence: 62%
“…A combination of microarray and other investigations have shown that the PrrA regulon includes tetrapyrrole biosynthesis genes (10,11,27,30,41), as well as genes with roles in many other biological processes, including photosynthesis, carbon and nitrogen fixation, denitrification, formaldehyde dehydrogenase activity, and aerotaxis (2,8,13,18,31). For hemA, two PrrA binding sites that are centered at bp ÏȘ163 and ÏȘ67 relative to the P1 transcription start site have been identified.…”
mentioning
confidence: 99%